Effect of cobalt on titania, ceria and zirconia oxide supported catalysts on the oxidative depolymerization of prot and alkali lignin. (March 2020) - Kumar, Avnish; Biswas, Bijoy; Bhaskar, Thallada
Highlights: Oxidative depolymerization of lignins with Co based metal oxides reported first time. Bio-oil (78 wt%) was obtained with prot lignin with Co/CeO2 catalyst. Acetosyringone (47.1%) was obtained with Co/CeO2 catalyst. Selective breaking of β-O-4 and α-β bond of both lignin(s) were observed. Abstract: The production of phenolics by oxidative depolymerization of prot lignin and alkali lignin were studied in the presence of cobalt impregnated TiO2, CeO2 and ZrO2 catalysts at 140 °C for 1 h. Maximum bio-oil yield of 78.0 and 60.2 wt% were observed with Co/CeO2 catalyst for prot lignin and alkali lignin, respectively. The characterizations of the bio-oils were carried out using GC–MS, FTIR, and 1 H NMR. The GC–MS compounds have been classified into four categories (G, H, S-type and others). The depolymerization of prot lignin showed a mixture of G, H and S type phenolic monomers. Interestingly, higher selectivity of acetosyringone (47.1%) was obtained in the presence of Co/TiO2 catalyst with prot lignin. The depolymerization of alkali lignin exhibited only G-type phenolic monomers production, and was effectively produced 67.4% (G-type monomer) in the presence of Co/ZrO2 catalyst.